Research trends of acupuncture therapy for hypertension over the past two decades: a bibliometric analysis - Man, Tian-Ming; Wu, Liu; Zhang, Jing-Yi; Dong, Yu-Ting; Sun, Yi-Tao; Luo, Ling (Cardiovascular diagnosis and therapy, 2023)
Acupuncture has already been extensively utilized to treat high blood pressure (hypertension) in several nations. Nevertheless, the bibliometric research on the worldwide usage of acupuncture for hypertension is mostly unclear. As a result, our objective for the research aimed to investigate the present state as well as developments in the global usage of acupuncture on hypertension during the last 20 years using CiteSpace (5.8.R2). The Web of Science (WOS) database examined papers on acupuncture treatment of hypertension from 2002 to 2021. We examined the number of publications, cited journals, nations/regions, organizations, authors, cited authors, cited references, and keywords utilizing CiteSpace. The record of 296 documents was obtained between 2002 and 2021. The quantity and frequency of annual publications rose gradually. Regarding frequency and centrality of citations, Circulation and ( ) scored top and second respectively. China had the most publications among countries/regions, as well as the five largest institutions were also in China. Cunzhi Liu was the most productive author, while P Li was the most referenced author. XF Zhao produced the first article inside the quantity of cited references classification. 'Electroacupuncture' had a significant frequency with centrality for the keywords, which suggested electroacupuncture is a popular treatment in this field. In the treatment of hypertension, electroacupuncture has a beneficial effect on reducing blood pressure. However, because of the many different applications of electroacupuncture frequencies in research, whether the electroacupuncture frequency is connected to the therapeutic impact should be given more significant consideration. The findings of this bibliometric analysis give an overview of the present state as well as developments of clinical studies on acupuncture for hypertensive patients during the last two decades, which could assist researchers in identifying hot subjects and exploring novel directions in further study within the field.